EFEKTIVITAS JAMUR Rhizoctonia binukleat TERHADAP PENERKEMBANGAN PATOGEN BUSUK BATANG VANILI (Fusarium oxysporum f.sp. vanillae) SECARA IN VITRO - Haryuni, Haryuni (JURNAL ILMIAH AGRINECA, 2014)
Fusarium oxysporum f.sp. vanillae is a pathogenic fungi for vanili plants. The fungi have chitincell wall that can be degraded by chitinase from chitinolytic Rhizoctonia binucleate of fungi.Aim of this research was determine how the interaction between the F. oxysporum f.sp. vanillaeand Rhizoctonia binucleate were isolated from plant rizosfere. Chitinolytic activity weremeasured based on the clear zone around the colony in chitin medium. Interaction of fungi weredetermined by an antagonistic test. This research showed that Rhizoctonia binucleate ischitinolytic, antagonist and alternative of biofungiside to F.oxysporum f.sp. vanillae.